Unpreparedness of Indonesian Madrasah Teachers in Utilizing Technology for Digital Religious Learning-Teaching - Pabbajah, Mustaqim; Hassan, Zainudin; Juhansar, Juhansar; Widyanti, Ratri Nurina; Fitria, Ai Zakiah (Jurnal Tarbiyatuna, 2025)
The adaptability of education systems to technological change is a critical and inevitable demand. This study explores the unpreparedness of Indonesian madrasah teachers in adapting to the ongoing digitalization of religious education. Using a grounded qualitative approach with descriptive analysis, data were collected through observations, interviews, and document analysis. The findings reveal that teachers struggle to adapt to digital-based religious instruction, primarily due to difficulties operating technological tools. This unpreparedness is further exacerbated by limited technological infrastructure and low levels of digital literacy among teachers. As a result, the effectiveness of religious education is hindered, and instructional time is often used inefficiently. The study underscores the urgent need to improve technological infrastructure and enhance teachers’ digital competencies to better support the digital transformation of education in Indonesia.